PENDUGAAN PARAMETER DEMOGRAFI DAN POLA PENYEBARAN SPASIAL WALABI LINCAH (Macropus agilis papuanus) DI KAWASAN TAMAN NASIONAL WASUR STUDI KASUS DI SAVANA CAMPURAN UDI-UDI SEKSI PENGELOLAAN III WASUR, PAPUA - Yanto Santosa; Fredy Sitorus (Department of Forest Resources Conservation and Ecotourism - IPB University, 2008)
The aim of the study was to know the population condition in savannah invaded by plant of Melaleuca sp and Eucalyptus sp specially disavan of mixture Ud-Udi. Useful research as reference data in nimble population walabi management in Wasur National Park. Method used of strip transect and plot the swampy forest animal. Perception conducted at three band that is band ecoton, savana band which abut the ecoton and band of mixture savana. This research is executed by during one month that is from april until may 2008. From result invetarisation obtained by that average of density the nimble walabi at Udi-Udi mixture savana is 0,67 tail per hectare. Highest density that is at band ecoton with the density 1,67 tail per hectare. From this result is known that by the nimble walabi prefer to be at the band ecoton compared to by band of mixture savannah which abut the forest of mixture and band of mixture savana. This density is compared to by smaller of density of savana ukra (pure savana not yet invasion). Structure old age the nimble walabi with the adult composition 17 tail (77,27%), 2 tail (9,09%) and child 3 tail ( 13,64%). Sex-ratio of reproduction at nimble walabi is sex-ratio at adult walabi, adult female and adult masculine comparison is 1 1. Totalizeing child individual is 3 adult female individual amount and tail is 9, is hence obtained by a harsh birth value of nimble walabi in Udi - Udi of mixture savana of equal to 33%. Nimble walabi mortality in Udi - Udi of mixture savana difficult to be known. From perception activity in field is not found by a dead individual. Pursuant to result analyse the test of chi square , obtained by pattern of nimble spreading spasial walabi in Udi - Udi savana is group in band ecoton by ID = 3,52 (more than 1 group d= 12,36; d > 1,96 group).Keywords: nimble walabi, population, and pattern of spreading spasial